PENGARUH KURVALINIER KEPERCAYAAN INTRATIM PADA KINERJA TIM ONGOING: PERAN PEMODERASIAN INTERDEPENDEN TUGAS - , Handrio Adhi Pradana ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Trust was suspected to have a dark side that can harm organizational performance. However, empirical support is less a serious concern. The issue of context of specific team was also believed to affect the dynamics of trust among the team members. In addition, intrateam trust which included in the emergent state framework allows situational factors, task interdependence, to become contingency between the relationship. This study sought to examine non-linear effects of intrateam trust on ongoing team performance with task interdependence as moderating variable. Hypotheses testing is performed by hierarchical regression analysis. Although the data from 63 hospital nursing care teams can not confirm all of the proposed hypotheses, alternative explanations of concepts, methodologies, and contexts are able to bridge the gap between hypotheses and research results. A number of issues related to data analysis and measurement is also a part of the interesting discussions.